Cross country - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series, 2008)
When the home of Alex Cross's oldest friend, Ellie Cox, is turned into the worst murder scene Alex has ever seen, the destruction leads him to believe that he's chasing his most dangerous enemy yet. As Alex and his girlfriend, Brianna Stone, become entangled in the deadly Nigerian underworld of Washington D.C., what they discover is shocking: a stunningly organized gang of lethal teenagers headed by a powerful, diabolical man-the African warlord known as the Tiger. Just when the detectives think they're closing in on the elusive murderer, the Tiger disappears into thin air. Tracking him to Africa, Alex knows that he must follow. Alone.